ANALISIS SUMBER PERMODALAN YANG DIAKSES OLEH UMKM (STUDI KASUS DI KOTA MALANG) - Luthfi, Khairan; Ashar, Khusnul (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aims to understand: a. Strategy done by umkm in overcoming limitations capital; b. Capital which institution chosen by lot MSMEs in asking credit .This study took a case study on MSMEs in  the Malang City. Research method used is  descriptive with qualitative approach phenomenology .This research result having two findings: first , that the owner of MSMEs in Malang  City  do  strategy  of  capital  to  the  banking  institution  some  others  borrow  to  the cooperative , friends or family as well as some more selling personal belongings .Second , in this research largely informants borrow capital in banking institution namely Bank Rakyat Indonesia.   Keyword: MSMEs (UMKM), Capital Resources, Credit